Modern Islamic Boarding School Governance: Institutional Management, Human Resources, Economic Independence And Branding At Al-Zaytun Islamic Boarding School - Sukma Bangkit Panji Muslim; Ade Titi Solihati; Meity Suryandari (JMPI: Jurnal Manajemen, Pendidikan dan Pemikiran Islam, 2026)
The modernization of Islamic boarding school (pesantren) management has become an important issue in strengthening the competitiveness and sustainability of Islamic educational institutions in the contemporary era. However, studies examining pesantren governance through an integrated perspective that combines institutional management, human resource development, economic independence, and branding strategies remain limited. This study aims to analyze the governance revitalization implemented at Al-Zaytun Islamic Boarding School through these four dimensions. Al-Zaytun was selected as a case study because it represents one of the largest modern pesantren in Indonesia with an integrated educational, economic, and organizational management system. This research employs a qualitative descriptive approach using a case study method. Data were collected through observations, document analysis, and literature review. The findings reveal that Al-Zaytun has implemented an integrated governance model that combines religious education, professional institutional management, economic empowerment, and strategic branding. Its bureaucratic-transformative leadership pattern is supported by structured human resource management and productive business units that strengthen financial independence. In addition, digital communication and branding strategies contribute to maintaining public trust and institutional reputation. Practically, the findings provide a reference for pesantren managers in developing professional, sustainable, and adaptive governance systems while preserving Islamic educational values. The study concludes that the governance model implemented at Al-Zaytun offers a valuable framework that can be adapted by other pesantren seeking to strengthen institutional quality, economic resilience, and public legitimacy in the era of globalization.